Microsporogenesis and micromorphology of pollen grains of the plant Alcea rosea (Malvaceae) - Rincón-Barón, Edgar Javier; Torres-Rodríguez, Gerardo Andrés; Passarelli, Lilian M.; Zarate, Diego A; Cuarán, Viviana Lucia; Plata-Arboleda, Sayonara (Revista de Biología Tropical, 2021)
Introduction: Studies on microsporogenesis, micromorphology and structure of pollen grains in Malvaceae are scarce. Objectives: To describe the process of microsporogenesis and micromorphological aspects of pollen grains in A. rosea. Methods: Androphores were processed according to standard protocols for sectioning in paraffin. The obtained sections were stained with Safranin-Alcian blue, Aniline blue was used for immature and unfixed anthers and for resin sections of the androphores, Toluidine blue. Ultrathin sections were observed with transmission electron microscopy. For observation with scanning electron microscopy the material was fixed and dehydrated in 2.2 dimethoxypropane, dried to a critical point and coated with gold. Results: Anthers differentiate from a cell mass at the distal ends of the stamen filaments. The wall of the mature anther presents an outer layer of epidermal cells and an inner layer, the endothecium. Microspore mother cells divide by mitosis and then undergo meiosis to form tetrads. The tapetum is initially cellular and forms a single layer of cells and then loses cellular integrity by invading the microsporangium locule, forming a periplasmodia, by the time the pollen grains are released it degenerated. During sporodermis formation, exine is first deposited and then intine. Pollen grains are pantoporate, apolar, with radial symmetry, spheroidal, with spines, bacula, granules and microgranules. Tectum is perforated with foveolea arranged homogeneously over the whole surface and pollenkit is present. Exine is broad and consists of a thick 3.5 to 4 µm endexine and a thin ektexine (0.6-0.7 µm). The ultrastructure shows columellae forming the infratectum. Capitate glandular unicellular nectariferous trichomes covers the whole surface of the stamen filaments. Conclusions: The structure and development of the anthers follows the known patterns for angiosperms. Simultaneous microsporogenesis and centripetal deposit of the sporodermis have been previously described for Malvaceae.